Hubungan Obesitas dengan Kejadian Nyeri Lutut pada Lansia - Nency Martaria; Joshua Kurniawan; Fernando Nahaniel; Noer Saelan Tadjudin (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Obesity is one of commonly found problem, with the numbers rising globally. Obesity also often associated with other conditions, such as heart disease, stroke, diabetes, and osteoarthritis. This study aims to find out the correlation between obesity and incidence of knee pain for elderly. The study is an analytic observational study with cross-sectional design, that’s done at Sasana Tresna Werda RIA Pembangunan in January 2019. The population for this study is the elderly with minimum 60 years of age. Data were obtained through interview for knee pain variable, height and weight were measured by health workers using calibrated tools. Body mass index (BMI) over 25 kg/m2 is categorized as obese. Descriptive data will be presented as proportion (%). Statistical test used in the study are Pearson Chi Square with Yates Correction and Fisher Exact as alternative. The expected significance value in this study is 5%. The study found that there was significant relationship between obesity and knee pain in the elderly at Sasana Tresna Werda RIA Pembangunan (p-value=0.022). Elderly group with obesity is clinically known have 2.684 times higher riks of experiencing knee pain compared to the other group. Obesity is a major risk factor for knee pain including osteoarthritis and has an impact on morbidity in the elderly population. Holistic evaluation and treatment is needed in dealing with knee pain and obesity, considering that these two variables have a complex and multi-factorial pathogenesis.